Exploring Greek actinobacterial biodiversity for the discovery of bioactive metabolites with skin antiaging potential - Gaitanis, Konstantinos; Gkogkou, Eirini; Laskaris, Paris; Tsafantakis, Nikolaοs; Gianniou, Despoina D.; Kaili, Stavroula I.; Ntroumpogianni, Georgia C.; Theodosopoulou, Aikaterini; Milic, Nikola; Hatzinikolaou, Dimitris G.; Fokialakis, Nikolas; Trougakos, Ioannis P.; et al. (Frontiers in Microbiology, 2025)
Actinobacteria are a rich secondary metabolite source, accounting for nearly half of known bioactive microbial compounds, thus representing promising targets for novel bioactive molecule discovery. To explore potential antiaging compounds, we screened extracts from 980 actinobacterial strains isolated from diverse Greek ecosystems. Extracts were evaluated for elastase and tyrosinase inhibition in vitro, followed by toxicity and efficacy assessments in human cell lines. One Amycolatopsis and two Streptomyces strains exhibited significant tyrosinase inhibition, and one showed elastase inhibition, prompting further investigation. Culture optimization and fractionation of one of the most promising Streptomyces extracts resulted in the isolation of the six most bioactive and least toxic molecules, namely, Cyclo (L-proline-L-tyrosine) (1), Cyclo (Pro-Phe) (2), Lumichrome (3), P-(acetylamino) benzoic acid (4), Daidzein (5), and Uracil (6). These were tested for elastase and tyrosinase inhibition as well as antioxidant activity, and the activation of the autophagy-lysosome and the ubiquitin-proteasome system in cell lines and in Drosophila melanogaster. Molecules (1) and (4) demonstrated moderate elastase inhibition, while molecules (2), (3), (5), and (6) reduced reactive oxygen species under certain conditions. None activated the proteasome but all increased lysosomal activity in cell lines. Molecules (1), (2), (4), (6) were selected for study on Drosophila. Molecules (1) and (2) increased the activity of proteasome and molecules (1), (2), (4) increased the activity of lysosomes. All four molecules triggered antioxidant responses in Drosophila. This study highlights the potential of Greek actinobacterial biodiversity as a valuable resource for developing novel antiaging compounds with significant therapeutic implications for skin aging.